1988
DOI: 10.1212/wnl.38.5.743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vigabatrin on epilepsy in mentally retarded patients

Abstract: We studied the antiepileptic potency of vigabatrin (gamma-vinyl GABA, GVG) as an open trial in a group of 36 mentally handicapped patients with drug-resistant epilepsy (30 had seizures of partial onset and 6 had primary generalized [PG] tonic-clonic convulsions). With this treatment, 13 (43%) of the patients with seizures of partial onset and 2 (33%) with PG had more than 50% reduction in seizure frequency. The antiepileptic effect appeared during the first month of therapy and continued throughout the 7-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 1 publication
1
19
0
Order By: Relevance
“…Vigabatrin had no effect on plasma concentrations of carbamazepine, valproic acid, phenobarbital, clonazepam, clobazam, ethosuximide and oxcarbazepine (Cocito et al 1989;Gram et al 1985;Loiseau et al 1986;Luna et al 1989;Matilainen et al 1988). …”
Section: Drug Interactionsmentioning
confidence: 93%
“…Vigabatrin had no effect on plasma concentrations of carbamazepine, valproic acid, phenobarbital, clonazepam, clobazam, ethosuximide and oxcarbazepine (Cocito et al 1989;Gram et al 1985;Loiseau et al 1986;Luna et al 1989;Matilainen et al 1988). …”
Section: Drug Interactionsmentioning
confidence: 93%
“…With the exception of decreased hemoglobin levels noted in several children receiving VGB (38) and decreased granulocytes observed in a few adult patients (39), no clinically significant laboratory changes have been reported with VGB (28). Serum levels of liver transaminase are reported to be reduced in some patients during VGB administration (40), but these have not been associated with hepatic or renal dysfunction (28).…”
Section: Ltgmentioning
confidence: 99%
“…Several groups have reported changes in subjectively assessed aggression, irritability, and other mood components, 3 20 21 but other studies have shown no effect of vigabatrin on mood'819 and an overall improvement in quality of life and subjective wellbeing as assessed by questionnaire. '8 [21][22][23] Methods…”
mentioning
confidence: 99%
“…Several groups have reported changes in subjectively assessed aggression, irritability, and other mood components, 3 20 21 but other studies have shown no effect of vigabatrin on mood'819 and an overall improvement in quality of life and subjective wellbeing as assessed by questionnaire. '8 [21][22][23] Methods PATIENTS AND PROCEDURES Forty five outpatients with partial seizures refractory to optimal antiepileptic drug treatment were studied. Patients had shown an ability to keep an accurate seizure diary distinguishing between simple partial seizures, complex partial seizures, and secondary generalised seizures.…”
mentioning
confidence: 99%